PENERAPAN STUDENT TEAM ACHIEVEMENT DIVISIONS TERHADAP HASIL BELAJAR SISWA PADA MATERI MENULIS PUISI - Hendra (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
This study aims to determine the improvement of student learning outcomes and student activities using Student Team Achievement Division (STAD) type cooperative learning model in class. The method used in this study is classroom action research consisting of two cycles. The analysis technique in this study is instrument 1 about student learning outcomes testing and instrument 2 about student activity. The result of pretest showed the average of pretest ability of students was 33,6 and after applying the STAD type cooperative learning model, there was an increase in the first cycle, student learning outcomes become 68,0 and in the second cycle become 84,0. Based on the observation of student learning activity in the first cycle is 55% and in the second cycle becomes 93% Based on the above data, it can be concluded that the applying of the STAD type cooperative learning model can improve students’ poetry writing ability of MA Darul Qur’an 2018/2019 academic year.